Peningkatan Keterampilan Menulis Aksara Jawa melalui Model Pembelajaran Kooperatif Kartu Arisan - Windarti Windarti (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
The purpose of this study is to describe the improvement of Javanese script writing skills through the cooperative learning model using arisan cards for grade VII A students of SMP Negeri 5 Yogyakarta. This research is conducted through planning, action, observation and reflection stages. The research is conducted from January to March 2020 in three cycles. Data collection techniques use observation sheets and tests. learning outcomes indicate that; the learning process through the cooperative learning model of arisan cards provides a pleasant learning atmosphere, students dare to express their opinions, students have more control over the learning material, students have enthusiasm in learning to write Javanese script, students become more honest in writing Javanese script characters, students are more self-confidence, students practice to write Javanese script more often. This research shows that there is an enhancement in the results of Javanese script writing skills. The average achievement in pre-cycle is 59.68. Cycle 1 is 70.65, cycle II reaches 76.45 and cycle III is in average of 82.25. There is an improvement in classical completeness, namely pre-cycle of 25.80%, cycle I is 51.61%, cycle II classical completeness is 67.74% and cycle III is 87.09%. Based on these results it can be concluded that the cooperative learning model of arisan cards can improve Javanese script writing skills.